Combatting physical threats posed via digital means: the European Commission's developing approach to the sale of counterfeit goods on the Internet. Issue 3 (27th May 2018) - Farrand, Benjamin
ABSTRACT: The purpose of this paper is to trace the development of the EU's policies regarding the combatting of counterfeiting and in particular the establishment of the European Observatory on Counterfeiting and Piracy (later renamed the European Observatory on Infringements of Intellectual Property Rights). This paper will demonstrate how 'hard' legal regimes for the management of online sales of counterfeit items have been significantly limited by the lack of effective data on the scale of the phenomenon, as well as the reluctance of Internet platforms to tackle online infringements. Through the empowerment of the Observatory and its transferal to the European agency the European Intellectual Property Office (EUIPO) however, the EU has managed to establish its position as a cyber-security actor able to tackle online infringements of intellectual property rights. Through research into and identification of best practices concerning the quantification of counterfeit sales, information collection and sharing, and in facilitating coordination and cooperation between networks of private and public sector actors, the Observatory has taken on a key role in establishing online networks for proactively countering the sale and distribution of counterfeit products online. In this way, the Commission's facilitation of a network governance model has led to the development of a more effective means of combatting the threat posed by physical goods that are distributed via digital means.